Pengaruh Mekanisme Corporate Governance, Likuiditas, Ukuran Perusahaan, Struktur Modal dan Pertumbuhan Penjualan Terhadap Kinerja Keuangan - Suciyanti, Velissa Nadia; Azmi, Zul; Fitriana, Nur (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
This study is motivated by the decline in the performance of the healthcare sector, which has become a particular concern amid rising public awareness of the importance of health services. However, the stock performance of this sector has contracted. Based on data from the Indonesia Stock Exchange (IDX), in 2024 the healthcare sector index fell by 2.6488%, marking the largest decline compared to ten other sectors. This indicates a gap between the increasing demand for health services and the financial performance of healthcare companies. The purpose of this study is to examine the effect of corporate governance mechanisms (independent commissioners and audit committees), liquidity, firm size, capital structure, and sales growth on the financial performance of healthcare companies listed on the IDX for the 2020–2024 period. This research applies a quantitative method with an associative approach. Data were obtained through documentation of annual financial reports sourced from the official IDX website and company portals. The population consists of 37 healthcare companies, with samples selected using purposive sampling. Based on the criteria, 13 companies were chosen with a five-year observation period, resulting in 65 observations. The data were analyzed using multiple linear regression with SPSS version 26. The results show that liquidity, capital structure, and sales growth significantly influence financial performance, while independent commissioners, audit committees, and firm size have no effect. These findings emphasize the importance of effective financial management and sales growth strategies in enhancing the performance of healthcare companies.